Legal Protection for Minority Shareholders in Public Companies: Analysis Based on Law Number 40 of 2007 concerning Limited Liability Companies - Dimas Adika Ardiyanto; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2023)
A Limited Liability Company is a legal entity in the form of a business entity whose capital consists of shares and whose shareholder partners have limited liability in proportion to the number of shares they own. As a consequence of the GMS decision, the rights and obligations of minority shareholders are the focus of this research. The company's actions were considered inconsistent, discriminatory and unjustified. This research aims to examine the legal protection for minority shareholders in public companies as outlined in Law no. 40 of 2007 concerning Limited Liability Companies in a comprehensive, straightforward and careful manner. It is hoped that this study will produce scientific, practical and scientific benefits for the author and anyone who wants to analyze it. This research method uses normative juridical research, which uses data from literature studies and the documents contained therein, as well as several supporting references. Secondary data consists of primary, secondary and tertiary legal materials, such as literature, scientific works and other library materials that discuss the materials used to create this scientific work. The results of this research indicate that the issue of legal protection for minority shareholders in public companies has been regulated in Law Number 40 of 2007 concerning Limited Liability Companies; however, the law has not been fully implemented. In other words, minority shareholders in public companies still have difficulty obtaining legal protection to obtain equity in the company.